Preparation of Fluorescent Materials from Biomass-Derived Furfural and Natural Amino Acid Cysteine through Cross-Coupling Reactions for Extended π-Conjugation - Tanaka, Shota; Ashida, Kana; Tatsuta, Go; Mori, Atsunori (Synlett, 2015)
Preparation of 2-furylthiazole-4-carboxylic acid methyl ester is achieved in four steps from biomass-derived heteroaromatic compound furfural and a natural amino acid l-cysteine. One-pot bromination and following palladium-catalyzed arylation with arylboronates of the thus obtained furylthiazole at the furan ring gives arylated furylthiazole in excellent yields. Further arylation at the C–H bond of the thiazole ring (5-position) in the presence of AgF as an additive leads to diarylated furylthiazoles, which show strong photoluminescence. Homocoupling at the C–H bond of thiazole is also carried out with AgF to afford the corresponding further conjugated product composed of eight (hetero)aromatic rings.
Keywords: furfural; l-cysteine; cross-coupling; π-conjugation; photoluminescence